Trade relations between Colombia and the Czech Republic : Business opportunities - Lukeš, Nataly; Daza Aramayo, Lourdes Gabriela, 1983-; Zajíček, Miroslav, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The goal of this thesis is to determine and analyze trade relations between the Czech Republic and Colombia and to identify concrete business opportunities among them. the sub goals include the comparison of macroeconomic, political and socioeconomic indicators, analysis of the trade flows of goods, to identify the top 10 products and to determine the competitive advantage of both countries by using Porter's model of national competitive advantage. Finally several business opportunities are identified and each of them is described in more detail. The used methods are description, analysis and comparison of data from the Trademap webpage, World Bank and official records and reports from both countries trade ministries.
Vedoucí práce: Lourdes Gabriela Daza Aramayo
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses